A Brief Review Using of Algae in Cosmetics - Jaffer, Ebtehal M.; Al-Shaheen, Maitham A. (Mesopotamian Journal of Marine Sciences, 2025)
Macro and microalgae found in lakes, rivers, and oceans have shown to be very important as a source of bioactive compounds for cosmetics in our daily lives. Algal bioactives are being studied more because they contain vitamins, antioxidants, essential fatty acids, polysaccharides, and pigments. The world needs more natural and long-lasting cosmetic ingredients. These things keep skin moist, protect it from UV rays, and fight free radicals, which makes it look and feel better. Even after using them for a long time, algae-based cosmeceuticals have been shown to work as well as other products.This is a rapidly growing and economically promising area of the biological technology industry. It promotes the use of renewable resources in the cosmetics industry and the health of the skin. The use of natural substances has increased significantly, particularly in cosmetics.The review aims to look into the ecological importance, characteristics, and usefulness of algae in cosmetics. It will focus on how rich algae are in vitamins, antioxidants, and essential fatty acids, and how they can be a safe, healthier, and cheaper alternative to synthetic products. Biotechnology has come a long way in the last few years, making it easier to get bioactive compounds from algae and clean them upThis has led to new ways to make things that work better and last longer. Using green chemistry and nanotechnology in cosmetics that contain algae extracts has led to new ways to make the natural ingredients more stable, effective, and able to penetrate the skin. As more people learn about products that are good for the environment and don't hurt animals, algae-based cosmetics, which combine scientific progress with care for the environment, are likely to have a big impact on the future of the beauty industry.